2012
DOI: 10.1021/nl301763r
|View full text |Cite
|
Sign up to set email alerts
|

Single Crystalline β-Ag2Te Nanowire as a New Topological Insulator

Abstract: A recent theoretical study suggested that Ag(2)Te is a topological insulator with a highly anisotropic Dirac cone. Novel physics in the topological insulators with an anisotropic Dirac cone is anticipated due to the violation of rotational invariance. From magnetoresistance (MR) measurements of Ag(2)Te nanowires (NWs), we have observed Aharanov-Bohm (AB) oscillation, which is attributed to the quantum interference of electron phase around the perimeter of the NW. Angle and temperature dependences of the AB osc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
65
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 29 publications
(57 reference statements)
9
65
1
Order By: Relevance
“…Furthermore, the spots pattern can be fully indexed to the monoclinic Ag 2 Te phase via lattice spacing and demonstrate that the nanowire growth is along the [010] direction down the [100] zone axis. All the structural and compositional results are consistent with prior reports [6]. Figure 2 shows the representative SEM image of thermoelectric device and single Ag 2 Te nanowire that we used for our experiments.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Furthermore, the spots pattern can be fully indexed to the monoclinic Ag 2 Te phase via lattice spacing and demonstrate that the nanowire growth is along the [010] direction down the [100] zone axis. All the structural and compositional results are consistent with prior reports [6]. Figure 2 shows the representative SEM image of thermoelectric device and single Ag 2 Te nanowire that we used for our experiments.…”
Section: Resultssupporting
confidence: 88%
“…Figure 5 shows the Seebeck coefficient as a function of the temperature measured from Ag 2 Te nanowire. As previous studies reported that Ag 2 Te is -type semiconductor [1,6,15], the Seebeck coefficient reveals negative values, confirming that the majority of charge carriers are electrons. The Seebeck coefficients also drastically change at 130 ∘ C, similar trend of the resistance.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The carrier mobility μ (μ = R H /ρ, where ρ is the resistivity) is 344.43 cm 2 v − 1 s − 1 . Although it is smaller than the reported value for a single Ag 2 Te nanowire prepared by solid state sintering methods, 44 this value is a distinct improvement compared with previous reports of colloidal Ag 2 ± δ Te nanoparticle films. 45 Five-electrode transport measurements were conducted on bulk-sized c-Ag 2-δ Te nanosheet assembled films using a physical property measurement system (PPMS).…”
Section: Xps Depth Profile Analysiscontrasting
confidence: 65%
“…Nanowires with a high surface-tovolume ratio are of special interest because the surface state conductivity is expected to overwhelm the parasitic transport through the nanowire bulk. [5][6][7][8][9][10] While the Dirac cone has been directly detected by angle-resolved photoemission spectroscopy (ARPES) of Bi 2 Te 3 , [11][12][13] 20,37,38 While most of these works focus on reducing the relative contribution to electrical transport from the bulk by enhancing the surface contribution via field-effect, resolving the linear dispersion relation of the surface states has not been attempted so far.Our experiments were performed using a single nanowire device equipped with two electrodes for resistance measurements and a global back gate (figure 1 a). Electrical contacts to the nanowire were prepared via common laser beam lithography and subsequent sputter deposition of Ti/Pt.…”
mentioning
confidence: 99%